2019
DOI: 10.5194/acp-19-14233-2019
|View full text |Cite
|
Sign up to set email alerts
|

Objective evaluation of surface- and satellite-driven carbon dioxide atmospheric inversions

Abstract: Abstract. We study an ensemble of six multi-year global Bayesian carbon dioxide (CO2) atmospheric inversions that vary in terms of assimilated observations (either column retrievals from one of two satellites or surface air sample measurements) and transport model. The time series of inferred annual fluxes are first compared with each other at various spatial scales. We then objectively evaluate the small inversion ensemble based on a large dataset of accurate aircraft measurements in the free troposphere over… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
82
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 98 publications
(89 citation statements)
references
References 49 publications
4
82
3
Order By: Relevance
“…These differences are similar to the magnitude of data-model differences between flux inversions, suggesting that transport model errors limit the ability of evaluating CO 2 flux estimates with aircraft-based measurements. This result is in contrast to Chevallier et al (2019), who found that data-model mismatches were not strongly impacted by the version of Laboratoire de Météorologie Dynamique (LMDz) transport model employed.…”
Section: /2019jd032029contrasting
confidence: 99%
See 2 more Smart Citations
“…These differences are similar to the magnitude of data-model differences between flux inversions, suggesting that transport model errors limit the ability of evaluating CO 2 flux estimates with aircraft-based measurements. This result is in contrast to Chevallier et al (2019), who found that data-model mismatches were not strongly impacted by the version of Laboratoire de Météorologie Dynamique (LMDz) transport model employed.…”
Section: /2019jd032029contrasting
confidence: 99%
“…The results of this study suggest that surface-based and space-based atmospheric CO 2 constraints provide consistent constraints on NEE fluxes and can be combined in a flux inversion framework. This result stands in contrast to earlier attempts to combine these data sets (Houweling et al, 2015) and suggests that the improved consistency between the data sets has been made possible by the considerable effort spent refining the ACOS retrieval algorithm (Chevallier et al, 2019;Eldering et al, 2017;Kiel et al, 2019;Miller & Michalak, 2020;O'Dell et al, 2018).…”
Section: Resultscontrasting
confidence: 74%
See 1 more Smart Citation
“…Why not using NEE derived from atmospheric inversions though (e.g. Jena CarboScope (Rödenbeck et al, 2018), CAMSv17r1 (Chevallier et al, 2005(Chevallier et al, , 2019 and CarbonTracker-EU (Peters et al, 2010)). At least, we know that this data capture some processes that contribute to IAV_NEP, which are not being captured with eddycovariance data (e.g.…”
Section: Specific Commentsmentioning
confidence: 99%
“…For the comparison with GPP, we used gridded monthly SIF GOME-2 (Köhler et al, 2015) retrievals from the far-red spectral range, and for the evaluation of NEE atmospheric inversion-based estimates from Jena CarboScope , CAMSv17r1 (Chevallier et al, 2005;Chevallier et al, 2019), and CarbonTracker-EU (CTE2018, Peters et al, 2010;van der Laan-Luijkx et al, 2017). We further include comparisons to the previous GPP and NEE upscaling products of Jung et al, 2011 (hereafter referred as Ju11).…”
Section: Independent Observation-based Productsmentioning
confidence: 99%